Fast and secure automatic retrieval of data from multi-vendor devices - The portuguese experience - Louro, Miguel; Guisado, Jaime; Fortunato, Carlos; Cura, Carlos; Antunes, Bruno; Areias, Miguel; Grossinho, Miguel; Pereira, Luís Pinto; Pimenta, Fernando (My University, 2013)
Nowadays protection systems generate large amounts of useful data. The most important of which are the oscillographic records, because they allow: fault location estimation; validation of relay settings; validation of coordination among protections. This important information traditionally resided in the protection units and could only be retrieved through vendor proprietary software. Retrieving this information could be conducted in two ways: a specialized technician had to physically go to the substation (expensive solution); by use of a slow analog modem with a tendency to breakdown (especially in remote areas exposed to lightning strikes) and a high probability to stop working due to communication errors. Recently EDP has begun to equip all the substations with an IP network through optical fiber. This fast and reliable network, which is also intended for other application other than remote access, eliminates the communication constraints. Due to technological differences the substations were, for this purpose, separated in two groups: Substations with a modern protection system complying with IEC 61850; Substations with older protection units for which a pilotproject was conducted using the communications gateway Kalkitech SYNC2000. This device communicates with protection units from several vendors, using standardized (ex.: IEC61850) or proprietary protocols (ex.: ABB SPABUS), and has mechanisms for retrieving oscillographic records. The usage of standard tools such as FTP and file sync programs proved to be cost effective and reliable to get the information to a central location.
Keywords: Oscillographic records; IEC61850; Data retrieval; IP network